Bits, Bytes, Power & Diplomacy - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Bits, Bytes, Power & Diplomacy," written by Walter B. Wriston for the United States Institute of Peace 1 April 1997. The original speech is located in MS134.001.013.00006.